Prenatal diagnosis of chromosomal sex investigation of amniotic fluid cells - Pérez, Manuel (2015)
The problem of prenatal diagnosis of sex before birth, given the prograso of scientific research methods, we may assert, no longer as an enigma. From the most remote civilizations that preceded us, to this day, the mystery remained throbbing, both the interest of the scientist as popular curiosity.